Central banking and the world's financial system (World Gold Council LondonGB)
Address four main topics viz. anti-flationary monetary policy in an environment of modest economic growth; preparations for EMU and the euro; safeguards for the world's financial system; and, the future role of gold as a reserve asset in the European system of central banks.
DC